Development of a provincial road safety management system in Thailand - Chatchawal Simaskul; Pichai Taneerananon; Soparth Pongquan; Kunnawee Kanitpong; Brannolte, Ulrich; Thai Health Promotion Foundation (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
In Thailand, studies have shown that there is a need for a systematic and reliable road safety and accident information as well as a management system. The present lack of such a system has hindered the use of knowledge based on traffic and safety sciences in traffic safety policy, plan, strategies fonnulation, and development of practical measures to improve road accident situation nationwide. However, recently in Year 2003, the government of Thailand cited road safety issue as one of vital national agendas. Many government related agencies together with transportation engineers and medical researchers have attempted to construct a systematic road safety management system in order to provide sufficient data and infonnation for developing preventive and mitigation measures. This dissertation describes the result of a research on Development of Provincial Road Safety Management System (PRSS). It is the first system ever developed for the country. It involved informal connection to get to the data source which is one of the key building blocks of the system. Its success is the combined effort of many dedicated people especially doctors in regional hospitals who have devoted their life-time work on reducing road crashes injuries. The objectives of the system are to bring existing traffic accident databases, for example, highway accident database, hospital admitted database which is normally stand-alone database into one system to promote the sharing of traffic accident inforn1ation among concerned agencies, and to disseminate the knowledge gained from the system to government officers, researchers, and practitioners. Various processes in the system cycle including development, construction, implementation, promotion, and dissemination are explained. The Highway Accident and Hospital's Injury Surveillance (IS) databases in 2001 - 2005 were employed for the development, demonstration, and analyses. Implementations of the system through trainings were carried out in Khon Kaen, Udon Thani, Nakhon Ratchasima, and Songkhla. It was found that speeding, single vehicle accident, accident during festival, motorcyclists, and pedestrians are of major concerns. Examples of pilot application of the system and measmrement of its effectiveness through the introduction of Road Safety Performance Indicators; RSPIs in Udon Thani are demonstrated here. Specifically, the RSPIndex and RSPI for Udon Thani are as follows: RSPIndices include number of accidents per 100,000 population, fatalities per 100,000 population, injuries per 100,000 population, number of accidents per 10,000 registered vehicles, fatalities per 10,000 registered vehicles, injuries per 10,000 registered vehicles. RSPIs for general information of hospitalized accidents consist of patients per 100,000 population and RSPI-road traffic injuries (%); and for road users information comprise of RSPI-injured road users per 100,000 population, RSPI-level of severity of road users (%), RSPI-alcohol use in injured road users (%), and RSPI-non use of helmet in injured road users (%). The research also proposed RSPIndex for Motorcycle accident comprising four RSPIs including RSPI-MClists fatalities per 100,000 population, RSPI-MClists fatalities per 10,000 registered motorcycle, RSPI-MClists injuries per 100,000 population, and RSPI-MClists injuries per 10,000 registered motorcycle. It is anticipated that the PRSS becomes a knowledge management system for road safety in the province that helps support and integrate the needs for current and future utilization and dissemination of traffic safety knowledge among road safety researchers and practitioners in Thailand. Recommendations of the research include three aspects: technical considerations of management system, implications from analysis results for safety improvement, and further researches and considerations of continuing support of such system
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Engineering, School of Engineering and Technology
Thesis (Ph.D.) - Asian Institute of Technology, 2008
Keywords: Traffic safety -- Thailand